2012
DOI: 10.1016/j.ccr.2012.10.023
|View full text |Cite
|
Sign up to set email alerts
|

JAK2/STAT5 Inhibition Circumvents Resistance to PI3K/mTOR Blockade: A Rationale for Cotargeting These Pathways in Metastatic Breast Cancer

Abstract: Hyperactive PI3K/mTOR signaling is prevalent in human malignancies and its inhibition has potent antitumor consequences. Unfortunately, single-agent targeted cancer therapy is usually short-lived. We have discovered a JAK2/STAT5-evoked positive feedback loop that dampens the efficacy of PI3K/mTOR inhibition. Mechanistically, PI3K/mTOR inhibition increased IRS1-dependent activation of JAK2/STAT5 and secretion of IL-8 in several cell lines and primary breast tumors. Genetic or pharmacological inhibition of JAK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
181
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 58 publications
8
181
0
1
Order By: Relevance
“…It is also noteworthy that STAT3 activation is observed in stem cell-like cancer cells from different molecular subtypes of breast cancer and targeting JAK2 is effective to treat the triple-negative subtype in preclinical models. [48][49][50] Together, these results suggest a pivotal role for JAK2 irrespective of the receptors mediating activation and thus underscore a generalizable potential for JAK2-targeted therapy to treat multiple forms of this disease.…”
Section: Discussionmentioning
confidence: 94%
“…It is also noteworthy that STAT3 activation is observed in stem cell-like cancer cells from different molecular subtypes of breast cancer and targeting JAK2 is effective to treat the triple-negative subtype in preclinical models. [48][49][50] Together, these results suggest a pivotal role for JAK2 irrespective of the receptors mediating activation and thus underscore a generalizable potential for JAK2-targeted therapy to treat multiple forms of this disease.…”
Section: Discussionmentioning
confidence: 94%
“…43 In addition, breast cancer cells reportedly can escape from the therapeutic inhibition of the phosphoinositide-3-kinase/mammalian target of rapamycin (PI3K/mTOR) signaling cascade by upregulating CXCL8 and hence activating alternative growth-stimulatory pathways. 44 Of note, high expression levels of CXCL8 or CXCR2 have been associated with worsened disease outcome in several types of cancer, including astrocytomas and lung adenocarcinoma. 45,46 Thus, it may appear paradoxical that the CXCL8/CXCR1-2 system is often constitutively active in cancer cells, mainly mediating pro-tumorigenic effects, yet can be hyperactivated by immunogenic chemotherapy to promote CRT exposure and ICD.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that a subset of cancer cells exhibited higher levels of JAK2 and S6K1 pathway activation compared with non-malignant cells and were strikingly sensitive to dual inhibition of these two kinases. Although JAK2 inhibitors are indicated for myeloproliferative neoplasms and are being evaluated for other cancers (5,8), certain types of cancers are likely to have limited responses to JAK2 inhibition alone (48,49). S6K1 is a primary downstream effector of mTORC1 signaling, and inhibition of this pathway has been known to cause a cytostatic effect in cancer cells rather than inducing cell death (18,50).…”
Section: Discussionmentioning
confidence: 99%